Medium Entropy‐Enabled High Performance Cubic GeTe Thermoelectrics - Shizhen Zhi (Advanced Science, 2021)
Abstract The configurational entropy is an emerging descriptor in the functional materials genome. In thermoelectric materials, the configurational entropy helps tune the delicate trade‐off between carrier mobility and lattice thermal conductivity, as well as the structural phase transition, if any. Taking GeTe as an example, low‐entropy GeTe generally have high carrier mobility and distinguished zT > 2, but the rhombohedral‐cubic phase transition restricts the applications. In contrast, despite cubic structure and ultralow lattice thermal conductivity, the degraded carrier mobility leads to a low zT in high‐entropy GeTe. Herein, medium‐entropy alloying is implemented to suppress the phase transition and achieve the cubic GeTe with ultralow lattice thermal conductivity yet decent carrier mobility. In addition, co‐alloying of (Mn, Pb, Sb, Cd) facilitates multivalence bands convergence and band flattening, thereby yielding good Seebeck coefficients and compensating for decreased carrier mobility. For the first time, a state‐of‐the‐art zT of 2.1 at 873 K and average zTave of 1.3 between 300 and 873 K are attained in cubic phased Ge0.63Mn0.15Pb0.1Sb0.06Cd0.06Te. Moreover, a record‐high Vickers hardness of 270 is attained. These results not only promote GeTe materials for practical applications, but also present a breakthrough in the burgeoning field of entropy engineering.